U‐Shaped Relationship Between White Blood Cell Counts and Incident Hypertension in Military Young Adults: The CHIEF Study, 2014–2020 - Kun‐Zhe Tsai; Chia‐Wei Hong; Yun‐Chen Chang; Wei‐Chun Huang; Xuemei Sui; Carl J. Lavie; Gen‐Min Lin (Immunity, Inflammation and Disease, 2025)
ABSTRACT Background Systemic low‐grade inflammation, which is characterized by increased counts of blood leukocytes (white blood cells, WBCs), can lead to hypertension, while reduced WBC counts caused by the use of some substances, e.g., alcohol, can also lead to hypertension. However, there have been no studies on the association between WBC counts and the risk of hypertension in young adults. Methods This cohort study conducted in Taiwan included a total of 2351 military personnel who were aged 18–39 years, were free of baseline hypertension and were followed up for incident hypertension from 2014 to the end of 2020. Resting blood pressure (BP) was measured during each annual health examination, while blood WBC counts and a biochemical panel were checked at baseline (2014). Incident hypertension was diagnosed as a systolic BP ≥ 130 mmHg and/or a diastolic BP ≥ 80 mmHg and/or the use of antihypertensive medications. Smooth curve fitting and multivariable Cox hazard proportional regression analysis, controlling for baseline sex, age, substance use, body mass index, BP, physical activity, serum uric acid level and kidney function, were used to determine the association between the baseline WBC count and incident hypertension. Results During a median follow‐up of 6.1 years, 885 participants (37.6%) developed incident hypertension. A smoothing spline curve revealed a U‐shaped relationship between the WBC count and incident hypertension, with a turning point for the WBC count of 6.00 × 103/μL. In the multivariable analysis, the WBC counts were classified into four quartiles, among which the 2ndquartile (5.56–6.40 × 103/μL) was treated as the reference because it included the turning point. The 1st (lowest) WBC count quartile (4.03–5.55 × 103/μL), the 3rd (high) WBC count quartile (6.41–7.43 × 103/μL) and the 4th (highest) WBC count quartile (7.44–10.97 × 103/μL) were associated with a higher risk of incident hypertension [hazard ratios and 95% confidence intervals: 1.50 (1.22, 1.83), 1.38 (1.14, 1.68) and 1.40 (1.16, 1.70), respectively]. The same pattern of association was observed across the sex, alcohol consumption, tobacco smoking, and physical activity subgroups. Conclusion Among military personnel, not only increased WBC counts but also reduced WBC counts, within normal limits, were associated with a greater risk of incident hypertension. Those with low WBC counts may be vulnerable to infection, which subsequently leads to an increase in BP.